Cathode materials, methods for their manufacture and uses
Patent Information
- Application Number
- JP2023580759
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-05-15
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2043-05-15
AI Technical Summary
【0013】 上記の技術案によれば、本発明の前記正極材料、その製造方法、及び使用は、以下の有益な効果が得られる。
Smart Images

Figure 0007640757000007 
Figure 0007640757000008 
Figure 0007640757000001
Abstract
Description
[Technical field]
[0001] CROSS REFERENCE TO RELATED APPLICATIONS This application claims the benefit of Chinese patent application No. 202210769645.6, filed on June 30, 2022, the contents of which are incorporated herein by reference.
[0002] The present invention relates to the field of lithium-ion batteries, and in particular to positive electrode materials, their methods of manufacture, and uses. [Background technology]
[0003] Layered ternary positive electrode materials include nickel-cobalt manganese oxide (NCM), nickel-cobalt aluminate (NCA) and their modified materials, which are currently mainly used in the positive electrode materials of lithium-ion batteries. With the rapid development of the lithium-ion battery related industry, the supply of raw materials corresponding to ternary positive electrode materials, especially cobalt raw materials, is becoming increasingly tight, the price is increasing, and the price pressure is constantly transmitted downstream. In addition, due to the influence of other factors such as the political situation in major cobalt ore exporting countries and child labor issues, as well as the potential risks of cobalt element to human health and environmental pollution, the development of cobalt-free positive electrode materials has already become a trend in the industry.
[0004] In the ternary system, the cobalt element mainly plays the role of stabilizing the material structure and improving the bulk phase diffusion of lithium ions, which is important for ensuring the capacity, rate characteristics and cycle stability of the ternary material. According to existing academic research, in the layered ternary system, when the cobalt element is removed, due to factors such as poor lithium diffusion kinetics, the layered cobalt-free material has problems such as low capacity and low initial efficiency, and often cannot meet the requirements for use.
[0005] One way to improve this problem is to increase the charge cutoff voltage of cobalt-free layered materials to achieve sufficient capacity. For example, a research team of Professor Sun Yangkook of Hanyang University in Korea has developed cobalt-free LiNi 0.9 Mn 0.1 By comparing and testing the electrical properties of the O2 material, they found that at a cutoff voltage of 4.4V, the material capacity is equivalent to that of NCM material with the same Ni content, but at 4.3V there is an obvious capacity difference.
[0006] Under the condition of high voltage use, lithium ion desorption can be ensured to a certain extent, but it will cause problems such as increased electrolyte side reactions and safety risks, and require further surface treatment. CN112186158A addresses the problems of cobalt-free high-nickel materials, such as poor initial charge / discharge efficiency and low capacity, by applying a surface composite carbon coating to a cobalt-free single crystal positive electrode material with a particle size of 3 to 5 μm and selecting graphene as the composite carbon, which can effectively increase the ionic conductivity of the cobalt-free positive electrode material, effectively isolate the electrolyte, reduce the occurrence of side reactions, and increase the initial charge / discharge efficiency of the material, but this measure requires an additional graphene coating process, which increases production costs.
[0007] The agglomerated material has a small particle size of primary particles and a certain proportion of voids inside the secondary particles, which is more favorable for ion exchange between the material and the electrolyte, ensuring the performance of capacity and rate characteristics. CN108199027A proposes an agglomerated cobalt-free positive electrode material and a synthesis method thereof, and by introducing niobium element doping during the sintering process, the high-rate discharge capacity and cycle stability of the material are greatly improved, but the capacity at low rates is not improved. Summary of the Invention [Problem to be solved by the invention]
[0008] In order to solve the problems existing in the prior art that the capacity and initial efficiency of the positive electrode material, especially the layered cobalt-free positive electrode material, are low, in the direction from the center to the surface of the secondary particles, a core structure, an intermediate layer, and a shell layer are included in this order, the intermediate layer is distributed in an annular shape, a specific relationship exists between the inner radius of the annulus and the radius of the secondary particles, the core structure is densely packed, the intermediate layer is porous, the shell layer is densely packed, and a positive electrode material having a network-like porous structure in the intermediate layer, a manufacturing method thereof, and uses are provided. The positive electrode material having the above specific structure has a high tap density, and a lithium-ion battery including the positive electrode material can have a high initial charge-discharge capacity, initial efficiency, rate characteristics, and high capacity retention rate.
Means for Solving the Problems
[0009] In order to achieve the above object, the first aspect of the present invention is Secondary particles formed by aggregation of primary particles, the secondary particles including a core structure, an intermediate layer, and a shell layer in this order in the direction from the center to the surface, the intermediate layer being distributed in an annular shape, and the inner radius r1 of the annulus and the radius R of the secondary particles satisfying the relationship 0.35 < r1 / R < 1, The secondary particles have a structure of a densely packed core structure - porous intermediate layer - densely packed shell layer, The porosity of the intermediate layer is 20% or more, The average pore diameter of the intermediate layer is 1 μm or less, and a positive electrode material is provided.
[0010] The second aspect of the present invention is Step (1) of mixing a nickel salt, an arbitrary M salt, and a compound containing an arbitrary M' element with a solvent to prepare a mixed salt solution, preparing a precipitant in a precipitant solution, and preparing a complexing agent in a complexing agent solution; Step (2) of charging the mixed salt solution into a reaction kettle containing the precipitant solution and the complexing agent solution in the presence of a protective atmosphere to perform a coprecipitation reaction; Mix a lithium source, the cathode material precursor, and any M' element-containing compound to obtain a mixed material. After sintering the mixed material in the presence of an oxygen-containing atmosphere, lower the temperature, crush it, sieve it to remove iron, and obtain the cathode material in step (3). The coprecipitation reaction is as follows: Control the temperature of the reaction system to T1 and perform the first-stage coprecipitation reaction until the median particle diameter D of the coprecipitation particles 50 reaches D1, and stop the input of the mixed salt solution in step (2-1). Control the temperature of the reaction system to T2 and, until the median particle diameter D of the coprecipitation particles 50 reaches D2, further input the mixed salt solution to perform the second-stage coprecipitation reaction, and stop the input of the mixed salt solution in step (2-2). Control the temperature of the reaction system to T3 and, until the median particle diameter D of the coprecipitation particles 50 reaches D3, further input the mixed salt solution to perform the third-stage coprecipitation reaction, and stop the input of the mixed salt solution in step (2-3). The coprecipitation slurry obtained in step (2-3) is aged, separated, washed, and dried to obtain the cathode material precursor in step (2-4). Step (3) provides a method for manufacturing a cathode material, where T1>T2 and 0.35<D1 / D3<1.
[0011] The third aspect of the present invention provides a cathode material manufactured by the above manufacturing method.
[0012] The fourth aspect of the present invention provides the use of the above cathode material in a lithium-ion battery.
Advantages of the Invention
[0013] According to the above technical solution, the cathode material, its manufacturing method, and use of the present invention can obtain the following beneficial effects.
[0014] The positive electrode material according to the present invention is a secondary particle formed by an aggregation of primary particles, and the secondary particles contain a core structure, an intermediate layer, and a shell layer, in that order, in the direction from the center to the surface, the intermediate layer is distributed in a circular ring shape with a mesh-like porous structure, and there is a specific relationship between the inner radius of the ring and the radius of the secondary particles. The positive electrode material having the above-mentioned specific structure has a high tap density, and can provide a lithium ion battery containing the positive electrode material with high initial charge / discharge capacity, initial efficiency, rate characteristics, and high capacity retention.
[0015] Furthermore, the positive electrode material according to the present invention has a structure of a densely packed core structure-a porous intermediate layer-a densely packed shell layer, and this makes it possible to further improve the initial charge / discharge capacity, initial efficiency, rate characteristics, and capacity retention rate of a lithium ion battery containing this positive electrode material.
[0016] Furthermore, in the present invention, the intermediate layer of the positive electrode material has a mesh-like porous structure and is distributed in a circular ring shape, the radial width (r2-r1) of the ring is appropriate, and the porosity and pore size of the porous structure allow sufficient impregnation with the electrolyte, facilitate ion exchange, shorten the lithium ion transport path, and reduce electrode polarization, thereby achieving high capacity expression and excellent rate characteristics, while at the same time buffering the volume change and structural stress of the secondary particles during lithium deintercalation and intercalation, maintaining the structural stability of the secondary particles, and extending the cycle life.
[0017] In the method for producing a positive electrode material according to the present invention, the secondary particles of the precursor have different crystallinity depending on the temperature of the co-precipitation reaction in the precursor growth stage and the particle diameter of the coprecipitated particles when they have different thicknesses. Furthermore, the secondary particles of the positive electrode material obtained by sintering this precursor contain a core structure, an intermediate layer, and a shell layer in this order from the center to the surface, the intermediate layer is distributed in a circular ring shape, there is a specific relationship between the inner radius of this ring and the radius of the secondary particles, and the secondary particles of the positive electrode material have different packing densities when they have different thicknesses.
[0018] Furthermore, in the method for manufacturing a positive electrode material according to the present invention, by controlling the temperature of the coprecipitation reaction and the particle diameter of the coprecipitated particles, the structure of the positive electrode material can be controlled. The process is easy to implement, the operation is simple, the temperature adjustment has high controllability, excellent stability, it is easier to control the growth particle size of the precursor as a monitoring means, it is suitable for mass production, and it can be implemented using the existing precursor manufacturing equipment as it is.
Brief Description of the Drawings
[0019] [Figure 1] It is an SEM image of the cross section of the secondary particles of the positive electrode material in Example 1 and the internal intermediate porous layer structure. r1 is the inner radius of the annulus of the intermediate layer, r2 is the outer radius of the annulus of the intermediate layer, and R is the radius of the secondary particles. [Diagram 2] It is an SEM image of the cross section and internal structure of the secondary particles of the positive electrode material in Comparative Example 1.
Modes for Carrying Out the Invention
[0020] The endpoints and any values within the ranges disclosed in this specification are not limited to the exact ranges or values, but should be understood to include values close to these ranges or values. In the case of numerical ranges, between the endpoint values of each range, between the endpoint values of each range and individual point values, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this specification.
[0021] The first aspect of the present invention is secondary particles formed by aggregation of primary particles. The secondary particles include a core structure, an intermediate layer, and a shell layer in this order in the direction from the center to the surface. The intermediate layer is distributed in an annular shape, and the inner radius r1 of the annulus and the radius R of the secondary particles satisfy the relationship of 0.35 < r1 / R < 1. The secondary particles have a structure of a densely packed core structure - porous intermediate layer - densely packed shell layer. The porosity of the intermediate layer is 20% or more. The intermediate layer has an average pore size of 1 μm or less.
[0022] In the present invention, according to the research of the present inventors, in the crystal structure of the conventional positive electrode material, the lithium diffusion kinetics is slow and the impregnation of the electrolyte is insufficient, so that the deintercalation / intercalation of lithium ions inside the bulk phase of the positive electrode material is difficult. As a result, the lithium ion battery obtained by using the positive electrode material has problems such as low capacity and low initial efficiency. As shown in FIG. 1, FIG. 1 is a cross-sectional view of the secondary particle of the positive electrode material of Example 1 and a schematic diagram of the structure of the intermediate network-like porous layer therein. As can be seen from FIG. 1, the layered cobalt-free positive electrode material according to the present invention has a secondary particle including a core structure, an intermediate layer, and a shell layer in this order from the center to the surface, and the intermediate layer is distributed in a circular ring shape, where r1 is the inner radius of the intermediate layer ring, r2 is the outer radius of the intermediate layer ring, and R is the radius of the secondary particle. When the inner radius r1 of the ring and the radius R of the secondary particle satisfy the above relationship, the porous structure of the intermediate layer of the positive electrode material can continue to a certain depth into the secondary particle, so that the electrolyte can be sufficiently impregnated into the secondary particle, the ion diffusion distance can be shortened, and the volume change during lithium deintercalation and intercalation can be buffered. Furthermore, a lithium ion battery including this positive electrode material can have high initial charge / discharge capacity, initial efficiency, rate characteristics, and high capacity retention.
[0023] Furthermore, according to the inventors' research, the crystal structure of conventional positive electrode materials has slow lithium diffusion kinetics and insufficient electrolyte impregnation, making it difficult to deintercalate and intercalate lithium ions inside the bulk phase of the positive electrode material. As a result, lithium-ion batteries obtained using the positive electrode materials have problems such as low charge / discharge capacity and low initial efficiency. The secondary particles of the positive electrode material according to the present invention have a structure of densely packed core structure-porous intermediate layer-densely packed shell layer, among which the densely packed core structure can ensure good contact between particles inside the positive electrode material, facilitate the transport of electrons / ions, and provide sufficient powder density. The porous intermediate layer can store the electrolyte, and can buffer the volume change and structural stress generated in the densely packed structure of the core structure and the shell layer during the process of lithium deintercalation / intercalation, thereby maintaining the stability of the secondary particle structure during repeated charging / discharging, reducing the occurrence of problems such as secondary particle rupture, powdering, and falling off, and extending the cycle life. Meanwhile, the electrolyte can enter the porous structure of the intermediate layer through the gaps between the primary particles of the densely packed shell layer, thereby providing a sufficient solid-liquid interface and buffer zone for lithium deintercalation / intercalation in the core structure, and further improving the discharge capacity and initial efficiency of a lithium-ion battery including the positive electrode material.
[0024] In the present invention, the porosity of the intermediate layer is determined from the ratio of the void area within the annular region of the intermediate layer to the annular area of the intermediate layer in a scanning electron microscope image of a cross section of a secondary particle of the positive electrode material, the void area and the annular area being measured by the grid method.
[0025] In the present invention, when the porosity of the intermediate layer satisfies the above range, it is indicated that the intermediate layer has a porous structure, and further, it is ensured that the secondary particles of the positive electrode material have the specific structure of the present invention.
[0026] As can be seen from FIG. 1, in the present invention, the intermediate layer of the secondary particles has a nanoscale porous structure, with a large number of pore structures and a uniform distribution. Therefore, when this positive electrode material is used in the electrode structure of a lithium-ion battery, the pore structure of the intermediate layer can accommodate a certain amount of electrolyte impregnated through the gaps between the primary particles of the shell layer. Compared with the dense packing structure of the secondary particles of the conventional positive electrode material, it can stably provide a richer solid-liquid contact interface, facilitate simultaneous ion exchange inside and on the surface of the secondary particles, shorten the transport path of lithium ions, reduce electrode polarization, achieve high capacity and excellent rate characteristics. The void structure provided by the intermediate layer also functions as a buffer layer against volume changes and structural stresses of the secondary particles during deintercalation / intercalation of lithium, can maintain the structural stability of the secondary particles during repeated charge and discharge, reduce the occurrence of problems such as destruction, pulverization, and shedding of the secondary particles, and extend the cycle life. Further, the present invention controls the distribution thickness of the intermediate layer in the secondary particles, that is, r2 / R - r1 / R, within a certain range, thereby avoiding negative effects such as a decrease in the density of the material powder and processability due to excessive voids inside the secondary particles, and risks to life and safety caused by side reactions due to excessive solid-liquid interfaces.
[0027] In the present invention, the average pore diameter of the intermediate layer is measured by a method of randomly selecting 20 voids in the intermediate layer in the SEM photograph of the cross-section of the secondary particles, measuring the longest pore diameter and the shortest pore diameter respectively, and calculating the average value. Furthermore, r1 / R is 0.4 to 0.7.
[0028] Furthermore, the intermediate layer has a network-like porous structure.
[0029] Furthermore, the porosity of the intermediate layer is 25 to 35%.
[0030] Furthermore, the average pore diameter of the intermediate layer is 300 to 500 nm.
[0031] According to the present invention, the outer radius r2 of the annulus of the intermediate layer and the radius R of the secondary particles satisfy the relationship of 0.5 < r2 / R < 1.
[0032] According to the present invention, when the outer radius r2 of the ring of the intermediate layer and the radius R of the secondary particle satisfy the above relationship, the intermediate layer of the positive electrode material is close to the surface of the secondary particle, facilitating impregnation with the electrolyte, while the dense shell layer plays a protective and support role and can maintain structural stability. Thus, a lithium-ion battery including this positive electrode material can have high initial charge / discharge capacity, initial efficiency, rate characteristics, and high capacity retention.
[0033] Furthermore, r2 / R is 0.7 to 0.9.
[0034] According to the present invention, r2 / R-r1 / R is 0.1 to 0.5.
[0035] In the present invention, when the inner radius r1 and the outer radius r2 of the ring of the intermediate layer satisfy the above relationship, the thickness of the intermediate layer of the positive electrode material can be ensured, and as a result, the number of internal porous structures is ensured, sufficient impregnation of the electrolyte is facilitated, and ion exchange is promoted. A lithium ion battery including this positive electrode material can have high initial charge / discharge capacity, initial efficiency, rate characteristics, and high capacity retention. In addition, the density is not reduced due to excessive voids inside the material, and the processability of the material is further ensured.
[0036] Furthermore, r2 / R-r1 / R is 0.2 to 0.4.
[0037] In the present invention, in the positive electrode material, the inner radius r1 of the intermediate layer ring, the outer radius r2 of the ring, and the radius R of the secondary particles are obtained by performing circle fitting and radius measurement on a cross-sectional SEM photograph of a secondary sphere of the positive electrode material.
[0038] According to the present invention, the average particle diameter D of the secondary particles 50 is 8 to 20 μm.
[0039] According to the present invention, when the average particle size of the secondary particles falls within the above range, the positive electrode material can achieve both a good powder density of the positive electrode material and a good discharge capacity of a lithium ion battery.
[0040] In the present invention, the average particle size of the secondary particles of the positive electrode material is measured by measuring the light scattering characteristics of the powder material dispersed in pure water using a laser particle size distribution measuring device.
[0041] According to the invention, the primary particles of the core structure are densely packed and spherical and / or quasi-spherical.
[0042] According to the present invention, the aspect ratio L1 of the primary particle of the core structure satisfies 1≦L1≦2.
[0043] In the present invention, the aspect ratio L1 of the primary particle of the core structure refers to the ratio of the longest axis length to the shortest axis length of the cross section of the primary particle in the internal densely packed portion in a scanning electron microscope (SEM) image of the cross section of the secondary particle of the positive electrode material.
[0044] In the present invention, when the aspect ratio L1 of the primary particles of the core structure satisfies the above range, it is possible to ensure that the primary particles of the core structure have a spherical and / or approximately spherical structure, thereby realizing dense packing in the core portion, improving contact between the primary particles, facilitating ion transport between the particles, and ensuring material density.
[0045] Furthermore, 1.2≦L1≦1.8.
[0046] According to the present invention, the primary particles of the shell layer are radially densely packed, and preferably the major axis directions of the primary particles of the shell layer are distributed in a radial direction toward the center of the secondary particles.
[0047] In the present invention, the aspect ratio L2 of the primary particles of the shell layer satisfies 2.5≦L2≦5.
[0048] In the present invention, the aspect ratio L2 of the primary particles of the shell layer refers to the ratio of the longest axis length to the shortest axis length of the primary particles densely packed adjacent to the surface of the secondary particle in a scanning electron microscope (SEM) image of a cross section of a secondary particle of the positive electrode material.
[0049] In the present invention, when the aspect ratio L2 of the primary particles of the shell layer satisfies the above range, the primary particles of the shell layer are densely packed radially, and the long axes of the primary particles are distributed radially toward the center of the secondary particles, thereby shortening the transport distance of the lithium ions inside the primary particles and making it easier to exhibit the capacity and rate characteristics. Meanwhile, the gaps between the particles make it easier for the electrolyte to be smoothly impregnated and accumulated in the void structure of the intermediate layer, facilitating the rapid deintercalation and intercalation of the lithium ions inside the secondary particles, reducing polarization and improving the rate characteristics. Furthermore, the shell layer densely packed radially can directionally release the structural stress caused by the volume change in the process of the secondary particles deintercalating and intercalating lithium, and can maintain the structural integrity of the secondary particles during repeated charging and discharging, thereby improving the lifespan.
[0050] Furthermore, 3≦L2≦4.
[0051] According to the present invention, the average particle size of the primary particles of the positive electrode material is 300 to 700 nm.
[0052] In the present invention, when the average particle size of the primary particles constituting the secondary particles satisfies the above range, it is possible to easily realize high-speed ion transport within the primary particles of the positive electrode material, and it is possible to ensure high capacity and rate characteristics of a lithium-ion battery containing this positive electrode material, while also controlling contact at the electrolyte-positive electrode material interface, reducing the occurrence of side reactions, and improving the strength of the particle structure of the positive electrode material, which is advantageous for maintaining a good cycle life of the lithium-ion battery.
[0053] Furthermore, the average particle size of the primary particles of the positive electrode material is 400 to 600 nm.
[0054] In the present invention, the average particle size of the primary particles of the positive electrode material is measured by a method in which 20 primary particles are randomly selected from a cross-sectional SEM image of secondary particles of the positive electrode material, the longest particle size and the shortest particle size of the cut surface are measured, and the average value is calculated.
[0055] According to the present invention, the tap density TD of the positive electrode material is 2.5 g / cm 3 or more, preferably 2.5 to 3 g / cm 3 It is. According to the present invention, the positive electrode material has the composition shown in Formula I: Li 1+a Ni x M y M' z O2 formula I (wherein, -0.1≦a≦0.2, 0.5≦x≦1, 0≦y≦0.5, 0≦z≦0.1, and x+y+z=1; M is at least one element selected from Mn, Al, Fe, and Mg; and M′ is at least one element selected from B, Mg, Al, Ca, Sr, Ba, Zr, Ti, Ce, Y, W, La, Nb, Ta, Zn, Co, and Mo.)
[0056] Furthermore, the positive electrode material is a layered cobalt-free positive electrode material.
[0057] In the present invention, the positive electrode material is a secondary particle formed by agglomeration of primary particles, the secondary particles include a core structure, an intermediate layer, and a shell layer in this order from the center toward the surface, the intermediate layer is distributed in a circular shape with a mesh-like porous structure, and a specific relationship exists between the inner radius of the circular shape and the radius of the secondary particles, so long as the positive electrode material has the characteristics described in the first aspect of the present invention, a lithium ion battery containing this positive electrode material can have high initial charge / discharge capacity, initial efficiency, rate characteristics, and high capacity retention. As for the manufacturing method of the positive electrode material, as long as it can manufacture the positive electrode material described in the first aspect of the present invention, it falls within the scope of protection of the present invention.
[0058] In the present invention, in order to further control the structure of the positive electrode material and endow the lithium-ion battery with the positive electrode material with high initial charge-discharge capacity, initial efficiency, rate characteristics and high capacity retention rate, preferably, the second aspect of the present invention also Step (1) of mixing a nickel salt, an optional M salt and an optional M'-element-containing compound with a solvent to prepare a mixed salt solution, preparing a precipitating agent into a precipitating agent solution, and preparing a complexing agent into a complexing agent solution; Step (2) of charging the mixed salt solution into a reaction kettle containing the precipitating agent solution and the complexing agent solution in the presence of a protective atmosphere to carry out a coprecipitation reaction; Step (3) of mixing a lithium source, the positive electrode material precursor and an optional M'-element-containing compound to obtain a mixed material, sintering the mixed material in the presence of an oxygen-containing atmosphere, then cooling, crushing, sieving to remove iron, and obtaining the positive electrode material, including The coprecipitation reaction is Controlling the temperature of the reaction system to T1 and performing a first-stage coprecipitation reaction until the average particle diameter D of the coprecipitation particles 50 becomes D1, and stopping the input of the mixed salt solution in step (2-1); Controlling the temperature of the reaction system to T2 and further inputting the mixed salt solution to perform a second-stage coprecipitation reaction until the average particle diameter D of the coprecipitation particles 50 becomes D2, and stopping the input of the mixed salt solution in step (2-2); Controlling the temperature of the reaction system to T3 and further inputting the mixed salt solution to perform a third-stage coprecipitation reaction until the average particle diameter D of the coprecipitation particles 50 becomes D3, and stopping the input of the mixed salt solution in step (2-3); Step (2-4) of aging, separating, washing and drying the coprecipitation slurry obtained in step (2-3) to obtain a positive electrode material precursor, and is carried out by Step (3) provides a method for manufacturing a positive electrode material, characterized in that T1>T2 and 0.35<D1 / D3<1.
[0059] In the present invention, the secondary particles of the precursor have different crystallinity depending on the temperature of the co-precipitation reaction in the precursor growth stage and the particle diameter of the coprecipitated particles when they have different thicknesses. Furthermore, the secondary particles of the positive electrode material obtained by sintering this precursor include a core structure, an intermediate layer, and a shell layer in this order from the center to the surface, the intermediate layer is distributed in a circular ring shape, there is a specific relationship between the inner radius of the ring and the radius of the secondary particles, and the secondary particles of the positive electrode material have different packing densities when they have different thicknesses.
[0060] Further, T1-T2≧15°C, and preferably T1-T2 is 15 to 40°C.
[0061] Furthermore, D1 / D3 is 0.4 to 0.7.
[0062] According to the present invention, |T1-T3|≦5°C.
[0063] In the present invention, by controlling the temperatures of the first and third coprecipitation reactions so as to satisfy the above-mentioned ranges, good crystallinity can be obtained both inside and on the surface of the coprecipitation product, and good crystallinity can be ensured in the resulting positive electrode material, which is advantageous for exhibiting electrical characteristics.
[0064] Furthermore, |T1-T3| is 2 to 5°C.
[0065] According to the present invention, 0.5 <D2 / D3<1である。
[0066] In the present invention, by controlling D2 / D3 so as to satisfy the above range, the electrolyte is quickly impregnated into the intermediate layer from the outside of the secondary particles and accumulated in the void structure, which is advantageous for improving the electrical properties, and also for obtaining a densely packed shell having a certain thickness, thereby maintaining the structural stability of the secondary particles.
[0067] Furthermore, D2 / D3 is 0.7 to 1, and preferably 0.7 to 0.9.
[0068] According to the present invention, D2 / D3-D1 / D3 is 0.1 to 0.5.
[0069] In the present invention, by controlling D2 / D3-D1 / D3 within a certain range, particularly when the above range is satisfied, the core densely packed inside, the intermediate porous layer, and the shell densely packed outside can all maintain appropriate thicknesses, and the advantages of each of the three structures can be fully exerted, resulting in ideal overall properties.
[0070] Furthermore, D2 / D3-D1 / D3 is 0.2 to 0.4.
[0071] According to the present invention, the T1 is from 60 to 80° C., preferably from 65 to 75° C., and the D1 is from 4 to 10 μm, preferably from 5 to 9 μm.
[0072] According to the present invention, the T2 is from 40 to 60° C., preferably from 45 to 55° C., and the D2 is from 6 to 18 μm, preferably from 7 to 14 μm.
[0073] According to the present invention, the T3 is from 40 to 80° C., preferably from 65 to 75° C., and the D3 is from 8 to 20 μm, preferably from 9 to 16 μm.
[0074] According to the present invention, the amounts of the nickel salt, the M salt, and the M' element-containing compound used are such that the molar ratio of n(Ni):n(M):n(M') is (0.5-1):(0-0.5):(0-0.1).
[0075] According to the present invention, the nickel salt and the M salt are each independently at least one selected from sulfates, chlorides, nitrates, and acetates.
[0076] According to the present invention, in step (1), the M' element-containing compound is at least one selected from sulfates, chlorides, nitrates, and acetates of M'.
[0077] According to the present invention, in step (3), the M' element-containing compound is at least one selected from the group consisting of oxide, hydroxide, and hydroxy-oxide of M'.
[0078] According to the present invention, the solvent is at least one selected from water, inorganic acids, alcohols, ethers, and amines.
[0079] According to the present invention, the precipitating agent is at least one selected from the group consisting of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium oxalate, potassium hydroxide, potassium carbonate, potassium bicarbonate, and potassium oxalate.
[0080] According to the present invention, the complexing agent is at least one selected from aqueous ammonia, ammonium sulfate, ammonium nitrate, ammonium chloride, salicylic acid, sulfosalicylic acid, and ethylenediaminetetraacetic acid. According to the present invention, the protective atmosphere is at least one selected from nitrogen gas, argon gas, air, and oxygen gas.
[0081] According to the present invention, the pH values of the first coprecipitation reaction, the second coprecipitation reaction, and the third coprecipitation reaction are each independently 9 to 13.
[0082] In the present invention, the amounts of the precipitant solution and the complexing agent solution to be added are not particularly limited as long as the pH of the first-stage coprecipitation reaction, the second-stage coprecipitation reaction, and the third-stage coprecipitation reaction in the reaction vessel is ensured to be 9 to 13.
[0083] In the present invention, the pH value of the first coprecipitation reaction, the pH value of the second coprecipitation reaction, and the pH value of the third coprecipitation reaction may be the same or different.
[0084] In the present invention, the concentrations of the precipitating agent solution and the complexing agent solution are not particularly limited, and conventional concentrations in the art can be adopted.
[0085] In the present invention, the coprecipitation reactions (first stage coprecipitation, second stage coprecipitation, and third stage coprecipitation) are carried out with stirring, and the rotation speed of the stirring is preferably 200 to 700 rpm, and more preferably 400 to 600 rpm.
[0086] According to the present invention, the amounts of the lithium source, the positive electrode material precursor, and the M' element-containing compound used are such that n(Li) / [n(Ni)+n(M)+n(M')] is 1 to 1.2:1.
[0087] According to the present invention, in steps (1) and (3), the amount of the M' element-containing compound used is such that n(M') / [n(Ni)+n(M)+n(M')] in the layered cobalt-free positive electrode material is 0 to 0.1, preferably 0 to 0.05.
[0088] According to the invention, the oxygen-containing atmosphere is selected from oxygen gas and / or air.
[0089] In the present invention, the concentration of oxygen gas in the oxygen-containing atmosphere is 20 vol % or more, preferably 50 to 100 vol %.
[0090] According to the present invention, the sintering conditions include a sintering temperature of 600 to 1000° C. and a sintering time of 6 to 20 hours.
[0091] In the present invention, the sintering conditions include increasing the temperature from 20-30° C. to 600-1000° C. at a rate of 0.3-5° C. / min, and maintaining the temperature for 6-20 hours.
[0092] Further, the sintering conditions include a sintering temperature of 650 to 900° C. and a sintering time of 7 to 15 hours.
[0093] Further, the sintering conditions include increasing the temperature from 20-30° C. to 650-900° C. at a rate of 0.5-3° C. / min, and maintaining the temperature for 7-15 hours.
[0094] A third aspect of the present invention provides a layered cobalt-free cathode material produced by the above-mentioned method.
[0095] A fourth aspect of the invention provides the use of the layered cobalt-free cathode material in a lithium-ion battery.
[0096] The present invention will now be described in detail with reference to examples. The morphology of the cathode material was characterized using scanning electron microscopy. The inner radius r1 of the ring of the intermediate layer of the secondary particle of the positive electrode material, the outer radius r2 of the ring, and the radius R of the secondary particle are obtained by performing circle fitting and radius measurement using a cross-sectional SEM photograph of a secondary sphere of the positive electrode material. The porosity of the intermediate layer of a secondary particle of the positive electrode material is determined by the ratio of the void area within a circular region of the intermediate layer to the circular area of the intermediate layer in a scanning electron microscope image of a cross section of a secondary particle of the positive electrode material, where the void area and the circular area are measured by a mesh method. The average particle size of the primary particles of the positive electrode material is measured by randomly selecting 20 primary particles from a cross-sectional SEM image of a secondary particle of the positive electrode material, measuring the longest particle size and the shortest particle size of the cut surface, and calculating the average value. The tap density (TD) of the cathode material is measured according to GB / T 5162 Tap Density of Metal Powders. All of the raw materials used in the examples and comparative examples are commercially available products. Example 1
[0097] (1) Nickel sulfate and manganese sulfate were added to water all at once so that the molar ratio of n(Ni):n(Mn) was 0.9:0.1 to prepare a mixed salt solution. (2) Sodium hydroxide solution was added as a precipitant and ammonia water as a complexing agent to the synthesis kettle. Before the coprecipitation reaction was started, nitrogen gas was introduced to create a protective atmosphere. The amount of the precipitant and complexing agent solutions was adjusted to control the pH of the solution system to 10.5. Then, the mixed salt solution was introduced in a confluence manner and stirred continuously to start the coprecipitation reaction. (2-1) In the first stage, the temperature of the solution system in the synthesis vessel was controlled at 70°C to carry out the first stage coprecipitation reaction. When the grown particle size of the coprecipitated particles in the solution system was monitored to be 8 μm, the supply of the liquid was stopped. (2-2) In the second stage, the temperature of the solution in the synthesis vessel was adjusted to 50°C, and the second stage coprecipitation reaction was carried out. When the grown particle size of the coprecipitated particles in the solution was monitored to be 12 μm, the supply of the liquid was stopped. (2-3) In the third stage, the temperature of the solution in the synthesis vessel was controlled at 65°C to carry out the third stage coprecipitation reaction. When the grown particle size of the coprecipitated particles in the solution was monitored to be 14 μm, the supply of the liquid was stopped. (2-4) The co-precipitation slurry is then transferred to an aging vessel, and after aging, solid-liquid separation, washing, and drying are performed to obtain the precursor material Ni 0.9 Mn 0.1 (OH)2 was obtained. (3) Lithium hydroxide, the above Ni 0.9 Mn 0.1 The (OH)2 precursor and TiO2 additive were mixed uniformly in a molar ratio of n(Li):[n(Ni)+n(Mn)]:n(Ti) of 1.02:0.995:0.005, then transferred to an atmospheric furnace, oxygen gas was continuously introduced to maintain the oxygen gas concentration in the furnace at >80 vol%, the temperature was raised to 800 °C at 3 °C / min, sintered for 12 h, and the temperature was naturally lowered to room temperature. The powder was then crushed and sieved to obtain the powder with a composition of Li 1.02 Ni 0.896 Mn 0.099 Ti 0.005 O2 positive electrode material A1 was obtained. Examples 2 to 13
[0098] Positive electrode materials were produced according to the method of Example 1, and the mixing ratio of the raw materials and the specific process conditions are shown in Table 1. Positive electrode materials A2 to A13 were obtained. All of the compositions of the positive electrode materials A2 to A13 contained Li 1.02 Ni 0.896 Mn 0.099 Ti 0.005 It's O2. Comparative Examples 1 to 5
[0099] Positive electrode materials were produced according to the method of Example 1, and the mixing ratio of the raw materials and the specific process conditions are shown in Table 1. Positive electrode materials D1 to D5 were obtained. The compositions of the positive electrode materials D1, D3, D4, and D5 all contained Li 1.02 Ni 0.896 Mn 0.099 Ti 0.005 O2, and the composition of the positive electrode material D2 is Li 1.02Ni 0.9 Mn 0.1 It's O2.
[0100] Table 1 [Table 1-1]
[0101] Table 1 (continued) [Table 1-2]
[0102] Table 2 shows the results indicating the structural characteristics of the positive electrode materials obtained in the examples and comparative examples.
[0103] Table 2 [Table 2-1]
[0104] Table 2 (continued) [Table 2-2]
[0105] FIG. 1 is an SEM image of the cross section and the internal intermediate porous layer structure of the secondary particle of the positive electrode material of Example 1, where r1 is the inner radius of the intermediate layer ring, r2 is the outer radius of the intermediate layer ring, and R is the radius of the secondary particle. FIG. 2 is an SEM image of the cross section and the internal structure of the secondary particle of the positive electrode material of Comparative Example 1. From FIG. 1 and FIG. 2, it can be seen that the multi-stage temperature-controlled synthesis method of the precursor proposed in the present invention can efficiently form a triple-layer structure of densely packed core-porous intermediate layer-densely packed shell inside the secondary particle of the positive electrode material.
[0106] As can be seen from Table 2, the positive electrode material produced in the examples of the present invention is secondary particles formed by aggregation of primary particles. The secondary particles include a core structure, an intermediate layer, and a shell layer in this order in the direction from the center to the surface. The intermediate layer is distributed in an annular shape, and the inner radius r1 of the annulus and the radius R of the secondary particles satisfy 0.4 < r1 / R < 1.
[0107] Furthermore, in the secondary particles of the positive electrode material produced in the examples of the present invention, the aspect ratio L2 of the primary particles in the shell layer is clearly different from the aspect ratio L1 of the primary particles in the core structure. Since the aspect ratio L2 of the primary particles in the shell layer is large, it is easy to form a radial structure, which is advantageous for ions to rapidly de-intercalate / intercalate and for the electrolytic solution to impregnate the intermediate porous layer along the gaps between the particles. On the other hand, since the aspect ratio L1 of the primary particles in the core structure is small, they become substantially spherical, enabling dense packing and ensuring the density of the material powder.
[0108] Furthermore, it was found from Table 2 that the addition timing of the M' element-containing compound does not significantly affect the structural parameters of the positive electrode material and the distribution of the porous intermediate layer of the secondary particles of the positive electrode material.
[0109] In the synthesis process of the precursor, if a multi-stage synthesis process (i.e., Comparative Example 1) is adopted to obtain a non-uniform crystalline precursor secondary particle structure, the porous intermediate layer structure characteristics cannot be realized in the corresponding positive electrode material. Since the filling inside the secondary particles is dense, the tap density TD of the positive electrode material is high.
[0110] On the other hand, if the growth particle size of the internal core of the positive electrode material is too small and the thickness of the intermediate layer is too large (i.e., Comparative Example 2), the inside of the secondary particles becomes too sparse and the tap density TD of the positive electrode material is too small. Test Example
[0111] Lithium-ion batteries were assembled using the positive electrode materials of the examples and comparative examples as follows. Specifically, the battery was assembled according to the following procedure.
[0112] First, the positive electrode materials produced in the examples and comparative examples, conductive carbon black, and polyvinylidene fluoride (PVDF) were weighed and mixed in a mass ratio of 95%:2.5%:2.5%, and NMP was added and stirred to make the mixture into a uniform slurry. The mixture was then applied onto aluminum foil, scraped evenly, dried, and then flattened by roller pressing. The mixture was punched out at a pressure of 100 MPa into a positive electrode plate with a diameter of 12 mm and a thickness of 120 μm, and then dried in a vacuum oven at 120° C. for 12 hours. The button battery assembly process was carried out in a glove box protected by Ar gas, with moisture and oxygen contents both less than 5 ppm. The positive electrode was the electrode plate obtained above, the negative electrode was a Li metal plate with a diameter of 17 mm and a thickness of 1 mm, the separator was a polyethylene porous film with a thickness of 25 μm, the electrolyte was a mixture of equal parts of ethylene carbonate (EC) and diethylene carbonate (DEC) with 1 mol / L of LiPF6 dissolved therein, and the battery case was a 2025-type button battery case. When assembly was completed, an unactivated battery was obtained.
[0113] The performance of the assembled lithium-ion batteries was tested, and the test results are shown in Table 3. The charging capacity of the lithium-ion batteries was measured by charging the button batteries, which had been left to stand for 2 hours after assembly, at room temperature with a constant current of 0.1C (1C=200mA / g) up to a cutoff voltage of 4.3V, and then charging them at a constant voltage for 30 minutes.
[0114] The discharge capacity was measured by discharging the button battery after charging at room temperature to 3.0 V at a constant current of 0.1 C. The initial efficiency was measured by dividing the 0.1C discharge capacity by the 0.1C charge capacity.
[0115] The 1C / 0.1C rate characteristics were measured by subjecting a button battery that had completed 0.1C charging and discharging at room temperature to constant current charging and discharging at 0.2C, 0.33C, 0.5C, and 1C in that order, resulting in a voltage window of 4.3 to 3.0V, and then dividing the 1C discharge capacity by the 0.1C discharge capacity.
[0116] The 80-cycle retention rate was measured by subjecting the button battery that had completed one charge / discharge at 0.1C described above to 80 cycles of constant current charge / discharge at 1C at room temperature in a voltage window of 4.3 to 3V, and dividing the discharge capacity at the 80th cycle by the discharge capacity at the 1st cycle.
[0117] Table 3 [Table 3-1]
[0118] Table 3 (continued) [Table 3-2]
[0119] From Table 3, it can be seen that the lithium ion batteries manufactured using the positive electrode materials having the porous intermediate layers manufactured in Examples 1 to 13 have high initial charge / discharge capacity, initial efficiency, and rate characteristics, as well as high capacity retention.
[0120] Furthermore, the characteristics of the positive electrode materials produced in Examples 1 and 2, such as r1 / R and r2 / R, are within the preferred ranges of the present invention, and thus the lithium ion battery obtained by using these positive electrode materials has further improved charge / discharge capacity, initial efficiency, rate characteristics, and capacity retention rate.
[0121] In Example 13, the porosity of the intermediate layer was too high and the average pore size was too large, which improved the initial capacity efficiency and rate characteristics. However, the density of the material powder was low and the porosity was too large, which reduced the structural strength of the intermediate layer and worsened the cycle retention rate.
[0122] The positive electrode material prepared in Comparative Example 1 did not have the characteristic structure of the porous intermediate layer of the present invention, and the impregnation of the electrolyte was slow, the initial efficiency and capacity were both low, and the rate characteristics were poor. The volume constantly changed during repeated de-intercalation and intercalation of lithium, which released the structural stress of the secondary particles and caused the secondary particles to be destroyed, resulting in a poor cycle life.
[0123] In Comparative Example 2, the core was designed to be too small and the porous intermediate layer was designed to be too thick, which is advantageous for the initial efficiency, capacity, and rate characteristics, but in the cycle test, there were too many side reactions on the surface, causing the capacity to decay quickly, and the low TD was also disadvantageous for practical use.
[0124] In Comparative Example 3, the intermediate layer was too close to the center of the secondary particles, which was disadvantageous for impregnation with the electrolyte, and the capacity, efficiency and rate characteristics in the first cycle were deteriorated.
[0125] On the other hand, Comparative Example 4 has a small sparse core, a densely packed intermediate layer, and a sparse shell, with the dense intermediate layer being the main structure, and its overall performance is superior to that of Comparative Example 1, but is clearly inferior to that of Example 1. In Comparative Example 5, the porosity of the intermediate layer was too small, so the average pore size was small and the impregnation of the electrolyte was limited, resulting in poor capacity, initial efficiency, and rate characteristics.
[0126] Although the preferred embodiment of the present invention has been described in detail above, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, the technical solution of the present invention may be modified in a number of simple ways, including combining each technical feature in another suitable manner, and these simple modifications and combinations should also be considered as the disclosed contents of the present invention, and all of them belong to the patent scope of the present invention.
Claims
1. A layered cobalt-free positive electrode material, comprising secondary particles formed by agglomeration of primary particles, the secondary particles including, in a direction from the center toward the surface, a core structure, an intermediate layer, and a shell layer, in that order, the intermediate layer being distributed in an annular shape, and an inner radius r1 of the annular shape and a radius R of the secondary particles satisfying a relationship of r1 / R of 0.4 to 0.7, an outer radius r2 of the intermediate layer and a radius R of the secondary particle satisfy the relationship that r2 / R is 0.7 to 0.9 and r2 / R-r1 / R is 0.1 to 0.5, The secondary particles have a structure of a densely packed core structure-a porous intermediate layer-a densely packed shell layer, The intermediate layer has a porosity of 25 to 35%; A positive electrode material, characterized in that the intermediate layer has an average pore size of 1 μm or less.
2. The intermediate layer has a mesh-like porous structure, The positive electrode material according to claim 1, wherein the average pore size of the intermediate layer is 300 to 500 nm.
3. The positive electrode material of claim 1, wherein r2 / R-r1 / R is 0.2 to 0.
4.
4. The average particle diameter D of the secondary particles 50 is 8 to 20 μm, the primary particles of the core structure are spherical and / or nearly spherical and closely packed; The aspect ratio L1 of the primary particle of the core structure satisfies 1≦L1≦2; the primary particles of the shell layer are radially densely packed; The positive electrode material according to claim 1 , wherein an aspect ratio L2 of the primary particles of the shell layer satisfies 2.5≦L2≦5.
5. The aspect ratio L1 of the primary particle of the core structure satisfies 1.2≦L1≦1.8, The positive electrode material according to claim 4 , wherein an aspect ratio L2 of the primary particles of the shell layer satisfies 3≦L2≦4.
6. The average particle size of the primary particles of the positive electrode material is 300 to 700 nm; The tap density TD of the positive electrode material is 2.5 g / cm 3 The positive electrode material according to claim 1 .
7. The average particle size of the primary particles of the positive electrode material is 400 to 600 nm, The cathode material according to claim 1, wherein the tap density TD of the cathode material is 2.5 to 3 g / cm 3 .
8. 2. The cathode material of claim 1 having a composition according to formula I: Li 1+a Ni x M y M' z O 2 Formula I (Here, -0.1≦a≦0.2, 0.5≦x≦1, 0≦y≦0.5, 0≦z≦0.1, and x+y+z=1; M is at least one element selected from Mn, Al, Fe, and Mg; and M′ is at least one element selected from B, Mg, Al, Ca, Sr, Ba, Zr, Ti, Ce, Y, W, La, Nb, Ta, Zn, and Mo.)
9. (1) mixing a nickel salt, an M salt and an M′ element-containing compound with a solvent to prepare a mixed salt solution, preparing a precipitant in a precipitant solution, and preparing a complexing agent in a complexing agent solution; (2) introducing the mixed salt solution into a reaction vessel containing a precipitant solution and a complexing agent solution in the presence of a protective atmosphere to carry out a co-precipitation reaction; (3) mixing a lithium source, the positive electrode material precursor, and any M′ element-containing compound to obtain a mixed material, sintering the mixed material in the presence of an oxygen-containing atmosphere, followed by lowering the temperature, crushing, and sieving to remove iron, to obtain the positive electrode material; The coprecipitation reaction is The temperature of the reaction system is controlled to T1, and the median particle diameter D of the coprecipitated particles is 50 A step (2-1) of performing a first-stage coprecipitation reaction until the concentration of the mixed salt solution becomes D1, and then stopping the introduction of the mixed salt solution; The temperature of the reaction system is controlled to T2, and the median particle diameter D of the coprecipitated particles is 50 (2-2) further introducing the mixed salt solution to carry out a second-stage coprecipitation reaction until the concentration of the mixed salt solution reaches D2, and then stopping the introduction of the mixed salt solution; The temperature of the reaction system is controlled to T3, and the median particle diameter D of the coprecipitated particles is 50 (2-3) further introducing the mixed salt solution to carry out a third-stage coprecipitation reaction until the concentration of the mixed salt solution reaches D3, and then stopping the introduction of the mixed salt solution; and step (2-4) of aging, separating, washing and drying the co-precipitation slurry obtained in step (2-3) to obtain a positive electrode material precursor. Step (3) is T1>T2, 0.35<D1 / D3<1, The method for producing a positive electrode material according to any one of claims 1 to 8, characterized in that M is at least one element selected from Mn, Al, Fe, and Mg, and M' is at least one element selected from B, Mg, Al, Ca, Sr, Ba, Zr, Ti, Ce, Y, W, La, Nb, Ta, Zn, and Mo.
10. T1-T2≧15° C., D1 / D3 is 0.4 to 0.7, |T1-T3|≦5° C., 0.5<D2 / D3<1, The method according to claim 9, wherein D2 / D3-D1 / D3 is 0.1 to 0.
5.
11. T1-T2 is 15 to 40°C, |T1-T3| is 2 to 5° C., D2 / D3 is 0.7 to 0.9, The method according to claim 10, wherein D2 / D3-D1 / D3 is 0.2 to 0.
4.
12. The T1 is 60 to 80° C., and the D1 is 4 to 10 μm. The T2 is 40 to 60° C., and the D2 is 6 to 18 μm. The manufacturing method according to claim 9, wherein T3 is 60 to 80° C. and D3 is 8 to 20 μm.
13. The T1 is 65 to 75°C, and the D1 is 5 to 9 μm, The T2 is 45 to 55° C., and the D2 is 7 to 14 μm. The manufacturing method according to claim 12, wherein the T3 is 65 to 75° C. and the D3 is 9 to 16 μm.
14. The amounts of the nickel salt, the M salt, and the M' element-containing compound used are such that the molar ratio of n(Ni):n(M):n(M') is (0.5-1):(0-0.5):(0-0.1); the nickel salt and the M salt are each independently at least one selected from a sulfate salt, a chloride salt, a nitrate salt, and an acetate salt; In step (1), the M' element-containing compound is at least one selected from sulfates, chlorides, nitrates, and acetates of M'; In step (3), the M' element-containing compound is at least one selected from the group consisting of oxide, hydroxide, and hydroxy-oxide of M'; the solvent is at least one selected from water, inorganic acids, alcohols, ethers, and amines; the precipitating agent is at least one selected from the group consisting of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium oxalate, potassium hydroxide, potassium carbonate, potassium bicarbonate, and potassium oxalate; the complexing agent is at least one selected from the group consisting of aqueous ammonia, ammonium sulfate, ammonium nitrate, ammonium chloride, salicylic acid, sulfosalicylic acid, and ethylenediaminetetraacetic acid; The protective atmosphere is at least one selected from nitrogen gas, argon gas, air, and oxygen gas; the pH values of the first coprecipitation reaction, the second coprecipitation reaction, and the third coprecipitation reaction are each independently 9 to 13; The amounts of the lithium source, the positive electrode material precursor, and the M' element-containing compound used are such that n(Li) / [n(Ni)+n(M)+n(M')] is 1 to 1.2:1; In steps (1) and (3), the amount of the M' element-containing compound used is set so that n(M') / [n(Ni)+n(M)+n(M')] in the layered cobalt-free positive electrode material is 0 to 0.1; The oxygen-containing atmosphere is selected from oxygen gas and / or air; The method according to claim 9, wherein the sintering conditions include a sintering temperature of 600 to 1000° C. and a sintering time of 6 to 20 h.
15. Use of the cathode material according to any one of claims 1 to 8 in a lithium ion battery.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery, method for producing same, and lithium secondary battery including the same
JP2018500720A